Does ochratoxin A (OTA) cause testicular cancer in humans? - SRINIVASA, Jayachandra (Acta medica Lituanica, 2011)
Ochratoxin A (OTA) is a naturally occurring contaminant of cereals, pigmeat, and other foods and is a known genotoxic in animals. It is a nephrotoxin and a carcinogen associated with Balkan endemic nephropathy and urinary tract tumours. It is also thought to be a cause of testicular cancer. A previous study has shown that consumption of foods contaminated with ochratoxin A during pregnancy induces lesions in testicular DNA of male offspring, and this supports a possible role for OTA in testicular cancer. Additionally, prenatal exposure to ochratoxin A in mice significantly depresses expression of the DMRT1 gene in male offspring, and the loss of this gene produces germ cell testicular tumours in mice. This molecular evidence supports the theory that ochratoxin A might be related to germ cell testicular tumours in mice and in humans.Keywords: ochratoxin A, testicular cancer, mycotoxins